Patient-doctor Concordance in Elderly Women’s Self-reported Health and Medical Records - Ockander, M.; Hjerppe, M.; Timpka, T. (Methods of Information in Medicine, 2002)
Objectives: To compare the chronic diseases mentioned by elderly women in an interview study with those documented in their respective medical records.Methods: The prevalence of positive diagnoses, overall agreement, and the kappa-coefficient were calculated for each group of diagnoses.Results: The lowest overall agreement was observed for psychiatric diseases, followed by diseases of the gastrointestinal system. Poor chance-adjusted agreement was found concerning diseases of the gastrointestinal system and diseases of the skin.Conclusions: The results suggest that a main reason for discordance was that the elderly women feared »losing face« by reporting some diseases.
Keywords: Diagnosis; women; medical records; patients; medical decision making